Focal dermal hypoplasia: a case with severe chest abdominal wall defect. - Oscherwitz, M.; Amin, S.; Hiremagalore, R. (European Journal of Pediatric Dermatology, 2024)
Focal demal hypoplasia is an X-linked dominant inherited skin disorder caused by mutations in the PORCN gene. A 1-day-old female neonate presented with a chief complaint of skin lesions after birth. She was born at 37- and 2/7-weeks’ gestation via vaginal delivery after the pregnancy was complicated by fetal growth restriction, chronic maternal hypertension, diet-controlled gestational diabetes mellitus, and maternal group B streptococcus colonization treated with ampicillin and gentamicin. Initial examination revealed multiple gestational abnormalities, including a severe chest and abdominal wall defect with an associated omphalocele, and bilateral oligosyndactyly affecting the patient’s feet. Here, we present her case, diagnostic evaluation, and the steps that led to the diagnosis of focal dermal hypoplasia.